The Impact of the First Wave of Covid-19 on the Financial Security of Economics Students in Higher Education - Kálmán, Botond; Bárczi, Judit; Zéman, Zoltán (Public Finance Quarterly, 2021)
Our study examines the financial literacy of students in higher education studying economics. Literature shows that financial literacy is becoming more valuable, but this increasingly important knowledge is not accompanied by practical results. Therefore, the sense of financial security is also reduced, especially if an unexpected major economic crisis occurs. The reasons for this decline have been investigated. Hungarian and foreign students were interviewed in a two-phase offline questionnaire survey. The first wave of COVID-19 took place between the two surveys to model the economic crisis. The questions assessed students’ theoretical knowledge, financial behaviour, and attitudes towards finance. We also asked how they rated their own financial situation and sense of security. After statistically processing the responses, linear models were set up to identify the factors that played a role in the development of financial security. Our most important result is that the year of the survey influences all dimensions of financial culture, which verifies the role and effect of the crisis caused by the outbreak.